2020
DOI: 10.1001/jamasurg.2020.0316
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mortality of Indigenous Populations Compared With Nonindigenous Populations

Abstract: IMPORTANCEA range of factors have been identified as possible contributors to racial/ethnic differences in postoperative mortality that are also likely to hold true for indigenous populations. Yet despite its severity as an outcome, death in the period following a surgical procedure is underresearched for indigenous populations.OBJECTIVE To describe postoperative mortality experiences for minority indigenous populations compared with numerically dominant nonindigenous populations and examine the factors that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…Our findings are consistent with inequities in surgical outcomes for Indigenous Peoples observed in other high income countries. [48][49][50][51] Although part of this effect may be attributable to the burden of chronic disease in Indigenous populations, our findings emerged by pooling results from studies that adjusted for important confounders, such as comorbidity status, which suggests that other factors may contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with inequities in surgical outcomes for Indigenous Peoples observed in other high income countries. [48][49][50][51] Although part of this effect may be attributable to the burden of chronic disease in Indigenous populations, our findings emerged by pooling results from studies that adjusted for important confounders, such as comorbidity status, which suggests that other factors may contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Aboriginal people that undergo surgical treatment, are younger, present at more advanced stages of disease and experience higher rates of post‐operative morbidity and mortality 5,6,40,62,63 . These poor health outcomes can reinforce distrust in clinicians and services and further hamper a willingness to seek health care.…”
Section: The Pathway To High‐quality Surgical Carementioning
confidence: 99%
“…The majority of literature exploring disparities in surgical outcomes come from the field of cardiac surgery 62,64,66,67 and there is a lack of studies investigating disparities other surgical specialties. In a recent systematic review exploring post‐operative mortality in Indigenous populations, seven Australian studies were identified all of which addressed cardiac procedures 6 . There is an urgent need for a better understanding of outcomes for Aboriginal people in all surgical specialties, to identify whether such disparities exist, and if so, how these may be mitigated to allow more effective and efficient deployment of surgery in Aboriginal communities.…”
Section: The Pathway To High‐quality Surgical Carementioning
confidence: 99%
See 1 more Smart Citation
“…Hétérogénéité : I 2 = 81 %, τ 2 = 0,0357, p < 0,01 Bresee et al 22 Leslie et al (poignet) 28 Leslie et al (colonne) 28 Leslie et al (hanche) 28 Goulet et al 26 Hong et al 27 Weber et al 43 Les conclusions concordent avec les iniquités dans les issues chirurgicales observées chez les Autochtones dans d'autres pays à revenu élevé [48][49][50][51] . Bien qu'une partie de cet effet puisse être attribuable au fardeau des maladies chroniques dans ces popula tions, nos conclusions portaient sur la combinaison de résultats corrigés pour les principaux facteurs confondants, comme les comorbidités, ce qui laisse croire que d'autres facteurs con tribueraient à la situation.…”
Section: Modèle à E Ets Aléatoiresunclassified